Asociación entre depresión y adherencia al tratamiento en pacientes con lupus eritematoso sistémico en el Hospital Nacional Dos De Mayo en el año 2017 - Castro Arredondo, Dayanna Stefany (2018)
Objectives: To determine the association between depression and adherence to treatment in patients with systemic lupus erythematosus in the National Hospital dos de Mayo in 2017. Material and methods: A cross-sectional analytical observational study was carried out. A total of 48 patients with a diagnosis of SLE were surveyed during the period corresponding to the study. Results: 93.8% were women and 6.3% were men. The mean age was 27.9 +/- 7.1 years, with a minimum of 17 years and a maximum of 41 years. 81.3% of the patients had secondary education, 75% came from Lima, and 39.6% were cohabitants. 47.9% of the patients had a slight level of depression. There was adherence to treatment in the 25% alone. We found that patients who presented depression did not adhere to the treatment for LE with a significant association p <0.05 and an OR = 9 (95% CI: 2.9 - 27). Conclusions: There is a statistically significant association between depression and adherence to treatment in patients with systemic lupus erythematosus at the National Hospital dos de Mayo in 2017.